Extrinsic apoptotic pathways: A new potential "Target" for more sufficient therapy in a case of cutaneous anaplastic large CD30+ ALK-T--cell lymphoma - Georgi Tchernev; Carlos Cardoso; Lubomir Arseniev; Hiroyuki Okamoto (Indian Journal of Dermatology, 2011)
The primary cutaneous T-cell lymphomas (CTCL) represent a clonal T-lymphocyte proliferation infiltrating the skin. CD30+ T-cell lymphomas present clinically as nodules with a diameter between 1 and 15 cm, mostly in elderly patients. The role of the CD30 molecule in patients suffering from T-cell lymphomas is not completely clear yet. The signal transduction pathway which includes CD30 seems to play a key role in tumor progression. In certain forms of T-cellular lymphomas, the interaction between CD30/CD30-ligand is able to provoke apoptosis of the "tumor lymphocytes". The modern conceptions of the pathogenesis of T-cell lymphomas include disorders in the pathways involved in programmed cellular death and disregulation in the expression of certain of its regulatory molecules. We are presenting an unusual case of a female patient with a primary cutaneous form of CD30 + /ALK− anaplastic large T-cell lymphoma. Upon the introduction of systemic PUVA, (psoralen plus ultraviolet light radiation) combined with beam therapy, a complete remission could be noticed. Eight months later, we observed a local recurrence, which was overcome by CHOP chemotherapy (Cyclophosphamide, Hydroxydaunorubicin (Doxorubicin), Vincristin (Oncovin®), Predniso(lo)n). Six months later, new cutaneous lesions had been noticed again. A new therapeutic hope for the patients with anaplastic large CTCL is actually based on the influence of the activity of the different apoptotic pathways. Death ligands, including tumor necrosis factor (TNF)-α, CD95L/FasL, and TRAIL, mediate also some important safeguard mechanisms against tumor growth in patients with CD30 + cutaneous anaplastic large T-cell lymphomas and critically contribute to lymphocyte homeostasis.